2011
DOI: 10.1080/00071668.2011.638620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy concentration, nonstarch polysaccharide concentration, and particle sizes of nonstarch polysaccharides on digesta mean retention time and gut development in laying hens

Abstract: 1. From an experiment with 504 laying hens (ISA Brown strain, 18-40 weeks of age), 90 40-week old hens were used for determining digesta mean retention time (MRT) and gut weight development. This experiment comprised 6 dietary treatments according to a 2 × 3 factorial design. Factors were dietary apparent metabolisable energy (AME) concentration (11·8 vs 10·6 MJ/kg), insoluble nonstarch polysaccharides (NSP) concentration (65 vs 134 g/kg), and fine vs coarse particle sizes of added NSP. Titanium recovery in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…This suggests that nutrient digestibility was improved by feeding silage, possibly in association with increased gizzard size and resulting improved digestibility as a result of the increased intake of fibre and larger size particles in silage. This apparent improvement in digestibility is supported by previous research where inclusion of large particle size materials (oat hulls, whole grain, wood shavings) improved starch digestibility in broilers and laying hens (Hetland and Svihus 2001;Hetland et al 2002Hetland et al , 2004van Krimpen et al 2011a).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This suggests that nutrient digestibility was improved by feeding silage, possibly in association with increased gizzard size and resulting improved digestibility as a result of the increased intake of fibre and larger size particles in silage. This apparent improvement in digestibility is supported by previous research where inclusion of large particle size materials (oat hulls, whole grain, wood shavings) improved starch digestibility in broilers and laying hens (Hetland and Svihus 2001;Hetland et al 2002Hetland et al , 2004van Krimpen et al 2011a).…”
Section: Discussionsupporting
confidence: 72%
“…It has been hypothesized that chickens have a requirement for structural components either in the diet or via foraging to stimulate development of, and passage through, the digestive tract (Hetland et al 2004;HarlanderMatauschek and Bessei 2005). The consumption of these components increases digestive tract capacity (Hetland and Svihus 2001), gizzard size and weight (Steenfeldt et al 2007;Singh et al 2014), and increased gizzard activity, which have been speculated to increase a bird's sense of satiation (Hetland and Svihus 2001;Hetland et al 2002;Steenfeldt et al 2007;van Krimpen et al 2011a). Therefore, the consumption of silage in the present research might be related to the uniform particle size and low fibre nature of the layer diet.…”
Section: Discussionmentioning
confidence: 74%
“…There was no such an increase in feed intake when there was no simultaneous supplementation of mannanase. Non starch polysaccharides (NSP) including mannan was known to increase digesta viscosity and to reduce feed intake in poultry (Van Krimpen et al, 2011). It is typical that the PKM contained 40~45% and 28~32% of NSP and mannan respectively (Sundu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Effect of dietary structure to a phytate-rich basal diet on precaecal P digestibility Dietary structure increased mean retention time in foregut of laying hens (Van Krimpen et al, 2011), although these findings were not confirmed in broilers (Hetland and Svihus, 2001;Svihus et al, 2002). Nevertheless, it is hypothesized that dietary structure would improve mixing of digesta with enzymes and acids, which are secreted by the proventriculus.…”
Section: Experiments (Chapter 3)mentioning
confidence: 93%